Using the Projection Gradient model To predict tourist demand in Iraq except for the Kurdistan Region - sabeeh lazim al kabi, Auday (International Journal of Psychosocial Rehabilitation, 2020)
The research aims to predict the touristic demand in Iraq through using the sample of projection gradient after limiting a time series from 2012 to 2019; therefore, the idea of research is taken from researches and studies of touristic economies in Iraq and the data of the central office of statistics . These references have pointed out that the touristic sector in Iraq has suffered from a significant defect, which is the inability to know the comers numbers of the next years. In fact, this is because of not using the methods that lead to many problems represented by unconsciousness of the comers importance to Iraqi lands and inability to know the comers. Actually, the touristic demand has various different forms in the touristic groups of the tourism committee of the ministry of culture and tourism. According to what is mentioned, may questions have arisen about the touristic demand in Iraq theoretically and practically, especially when the problem of study is restricted. The movement of the correct statistics. This is what gives the study importance, represented by the future of the tourism sector and touristic developments. Hence, the aims of research come to deal with the problems that the sector of tourism in Iraq suffers from . one of these is knowing the general line of touristic demand through orientating the responsible officials of touristic sector and adapting standard sample to take the touristic sector's role in Iraqi economy as being one of the solution in preceding the economic problems